2014
DOI: 10.1039/c4ta00341a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the nanostructure of bismuth telluride by selective chemical vapour deposition from a single source precursor

Abstract: † Electronic supplementary information (ESI) available: Details of substrate preparation and characterisation of the Bi 2 Te 3 thin lms; thermogravimetric analysis (TGA) of [BiCl 3 (Te n Bu 2) 3 ], SEM images of thin lms of Bi 2 Te 3 , Raman analysis of Bi 2 Te 3 thin lms, WDX compositional analysis of Bi 2 Te 3 thin lms, and microfocus and pole gure XRD analysis of micro-scale Bi 2 Te 3 arrays, lattice parameters rened for Bi 2 Te 3 grown on different substrates. See

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
(20 reference statements)
8
29
0
Order By: Relevance
“…(MO)CVD growth of single‐crystals platelets with partially controlled dimensions and orientation in arrays was reported in refs. . Here it is shown that the same level of crystal quality is reproduced on a pillar, rather than platelets geometry, and in a density that exceeds by orders of magnitude those reported in the above‐mentioned references.…”
Section: Resultssupporting
confidence: 68%
“…(MO)CVD growth of single‐crystals platelets with partially controlled dimensions and orientation in arrays was reported in refs. . Here it is shown that the same level of crystal quality is reproduced on a pillar, rather than platelets geometry, and in a density that exceeds by orders of magnitude those reported in the above‐mentioned references.…”
Section: Resultssupporting
confidence: 68%
“…Using atmospheric pressure chemical vapour deposition and a dual source precursor approach, SnCl 4 with either H 2 S or Et 2 Se can produce SnS 2 or SnS, 11,12 and SnSe 2 or SnSe, 13 respectively, depending on the conditions employed. A single source precursor approach, in which the metal and chalcogen are incorporated into one molecular compound, can lead to easier to handle precursors (since they are coordinatively saturated), potentially easier control of stoichiometry and, in some cases, the ability to deposit the binary material selectively onto specific regions of a patterned substrate on the micro- 14 or nano-scale. 15 While this substrate selectivity is rather atypical of CVD, it can be highly advantageous for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…In remarkable contrast, single source precursors for the solutionbased synthesis of high-quality Bi 2 Te 3 nanoparticles have not been reported to the best of our knowledge, while Read et al recently demonstrated that the bismuth chloride telluroether complex [BiCl 3 (TeBu 2 ) 3 ] is a suitable single source precursor for the MOCVD deposition of high-quality Bi 2 Te 3 thin films. [22] Herein we report on our attempts to prepare suitable single source and dual source precursors for the wet-chemical synthesis of crystalline Bi 2 Te 3 nanoparticles at rather mild reaction condition below 100 °C.…”
Section: Introductionmentioning
confidence: 99%